Antifungal prophylactic effectiveness and intrapulmonary concentrations of voriconazole versus posaconazole in lung transplant recipients. (29th August 2022) - Ju, Chunrong; Lian, Qiaoyan; Chen, Ao; Zhao, Boxin; Zhou, Shouning; Cai, Yuhang; Xie, Hui; Wei, Li; Li, Shiyue; He, Jianxing
Abstract: Invasive fungal diseases (IFDs) are one of the leading causes of death in lung transplant recipients. This study aimed to compare the antifungal prophylactic effectiveness, intrapulmonary and plasma levels of voriconazole with posaconazole in lung transplant recipients. This retrospective cohort study analyzed adult recipients who underwent lung transplantation between June 2017 and December 2020. Voriconazole oral tablets or posaconazole oral suspension was used for prophylaxis against posttransplant IFD. Drug concentrations in bronchoalveolar lavage fluid (BALF) and plasma were measured by using liquid chromatography-mass spectrometry. The 182 recipients included 142 in the voriconazole group and 40 in the posaconazole group. The trough plasma levels were comparable between voriconazole and posaconazole (1.65 ± 0.09 vs. 1.69 ± 0.03 μg/ml, P  = 0.55). However, the BALF levels were significantly higher for posaconazole than voriconazole (17.47 ± 11.51 vs. 0.56 ± 0.49 μg/ml, P  < 0.001). There was no significant difference in the total incidence of breakthrough IFDs between the voriconazole and posaconazole groups (10.6% vs. 7.5%, P  = 0.77). The intrapulmonary concentrations of posaconazole were significantly higher than voriconazole. The two agents had comparable antifungal prophylactic effectiveness.